Recombinant Adeno-Associated Viral Vector Production and Purification - Shin, Jin-Hong (2012)
Gene delivery vectors based on recombinant adeno-associated virus (AAV) are powerful tools for studying myogenesis in normal and diseased conditions. Strategies have been developed to use AAV to increase, down-regulate, or modify expression of a particular muscle gene in a specific muscle, muscle group(s), or all muscles in the body. AAV-based muscle gene therapy has been shown to cure several inherited muscle diseases in animal models. Early clinical trials have also yielded promising results. In general, AAV vectors lead to robust, long-term in vivo transduction in rodents, dogs, and non-human primates. To meet specific research needs, investigators have developed numerous AAV variants by engineering viral capsid and/or genome. Here we outline a generic AAV production and purification protocol. Techniques described here are applicable to any AAV variant.